How can sustainability science achieve impact for wicked problems such as climate change? - Vermeulen, Sonja J.; Campbell, Bruce M. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2011)
What are wicked problems? The example of agriculture under climate change. What do we know about tackling wicked problems? How can these principles and tools be applied to management of science in the CGIAR?